Pengaruh Cita Rasa dan Harga terhadap Minat Beli Konsumen pada Usaha Kecil Tahu Pak Jojon di Kp Jeletreng Bogor - Retno Wulansari; Ratih Andalusi; Sinta Sulistiani (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The increasing competition among small-scale food businesses requires business owners to maintain product quality and competitive pricing in order to attract consumer purchase intention. Taste and price are important factors influencing consumers in purchasing traditional food products, including tofu products produced by small enterprises. This study aims to analyze the effect of taste and price on consumer purchase intention at Tahu Pak Jojon Small Business in Jeletreng Village, Bogor. This research employed a quantitative approach using a survey method. The study involved 96 respondents selected using a census sampling technique. Research data were collected through the distribution of Likert-scale questionnaires to consumers of Tahu Pak Jojon. The collected data were processed using SPSS version 27 and analyzed through multiple linear regression analysis. The findings revealed that taste has a positive and significant effect on consumer purchase intention. Price also has a positive and significant influence on purchase intention. Simultaneously, taste and price significantly affect consumer purchase intention. The results indicate that consumers tend to purchase tofu products that offer good taste and affordable prices. Therefore, maintaining product taste consistency and setting competitive prices are essential strategies for increasing consumer purchase intention in small-scale food businesses.